(untitled) (Psychology Travelogs, 2025)
The issue of readiness for choosing a future profession and professional self-determination is one of the key aspects of the interaction between the individual and society, as well as an essential step in understanding the meaning of human life. This article analyzes major foreign concepts (S. Freud, K. Horney, M. Moser and others) that interpret professional self-determination as a continuous and long-term process. Such an approach emphasizes the necessity of providing individualized assistance to applicants in their career choice which includes discovering personal resources, creative potential, originality and uniqueness. At the same time, the article examines Ukrainian approaches (L. Olikhovska, H. Radchuk, I. Manokha, A. Bodnar, N. Makarenko among others) that interpret professional self-determination in close connection with personal self-determination, self-actualization, self-transformation and selfrealization in different life spheres, as well as the process of self-knowledge. In this regard, professional choice is not reduced to a single act of decision-making but is understood as a dynamic developmental trajectory shaped by internal motivations, social values and individual life goals. The comparative analysis of foreign and Ukrainian theories demonstrates the multidimensionality of professional orientation and highlights the role of psychological support in fostering readiness for career decision-making. The findings presented in the article emphasize the importance of forming value orientations, professional interests and individual responsibility for one’s own self-development. This approach allows to get a deeper comprehension of the mechanisms which underlay successful professional growth and personal fulfillment in contemporary social and cultural contexts.